Exploring Students Mathematical Understanding according to Skemps Theory in Solving Statistical Problems - Christina Monika Samosir; Jarnawi Afgani Dahlan; Tatang Herman; Sufyani Prabawanto (Didaktik Matematika, 2023)
Understanding a concept is not only for mastering the next concept. It is the foundational skill used to solve mathematical problems. This study aims to explore students' conceptual understanding.This research is qualitative research with phenomenology. The participants in this study consisted of 18 eighth-grade students from one of Bandung's private secondary schools. After the students were given the test, six students were selected as research subjects. This aims to ensure that data can be obtained thoroughly and comprehensively. Data collection techniques included tests, interviews, and observations, with research instruments comprising a test and an interview guideline. Data saturation has been achieved. The results of this study are as follows: 1) students with relational understanding are fewer in number than students with instrumental understanding. 2) students find it most difficult to use the interconnections of various mathematical concepts in solving problems. 3) students' difficulties are due to their lack of ability in the concept of basic operations and their lack of understanding of the problems. Therefore, teachers need to strengthen students' understanding of basic operations and the concepts of mean, mode, and median to effectively connect these concepts with their problems.